Polythore vexilla sp. nov. from southwestern Ecuador (Odonata: Polythoridae) - Tennessen, Kenneth J. (Zootaxa, 2024)
Polythore vexilla sp. nov. (holotype ♂, allotype ♀: ECUADOR, Azuay Province, small tributary of Río Pijilí, about 4.1 km SE of Victoria, -2.940°, -79.5625°; approximate elev. 730 m, 11-IV-2008, K. J. Tennessen leg., deposited in Florida State Collection of Arthropods) belongs in the Andean clade of Polythore Calvert. Based on genital ligula morphology it appears to be most closely related to P. gigantea (Selys). The male is distinct from all congeners by the narrow, medial black band in all four wings; the central band in the female wings is similar to the male.